“Desarrollo de una aplicación móvil con administración web para la gestión de comercialización y ventas de los productos de cerámica Agua Santa, ubicada en la ciudad Baños de Agua Santa”. - Casa Chanaluisa, Alex Wladimir (2021)
This technical proposal took place in Tungurahua Province, Baños de Agua Santa, where the lack of a digital platform for disseminating and selling ceramic products was a problem. The processes for the management of sales and product diffusion were in an archaic way. This process incurs an excessive use of time and limits potential customers' scope. Therefore, the technical proposal's objective is to develop a web application and mobile to systematize the sale and dissemination of ceramics using free software tools. For the project's development, the research methodologies were bibliographic research techniques. Data collection instruments were: interviews, observation, and surveys to understand the problem and identify the primary needs. Laravel, React JS, PHP, MySQL, Java, and Android Studio where the software used. An architecture pattern based on MVC was also applied using Scrum agile development methodologies for the web. Mobile -D in the mobile environment, and the UML modeling language for the diagrams' design, resulting in the systematization and automation in the ceramic sale and dissemination process, thus reaching a more significant number of clients and generating sources of work. In this way, with the implementation of the web and mobile applications in "Agua Santa" ceramics, the management of processes was optimized, increasing clients, workers, and owners engaged in ceramics' production distribution.